2020
DOI: 10.1021/jacs.9b10884
|View full text |Cite
|
Sign up to set email alerts
|

All-Carbon-Linked Continuous Three-Dimensional Porous Aromatic Framework Films with Nanometer-Precise Controllable Thickness

Abstract: Inherently porous materials that are chemically and structurally robust are challenging to construct. Conventionally, dynamic chemistry is thought to be needed for the formation of uniform porous organic frameworks, but dynamic bonds can limit the stability of these materials. For this reason, all-carbon-linked frameworks are expected to exhibit higher stability performance than more traditional porous frameworks. However, the limited reversibility of carbon−carbon bondforming reactions has restricted the expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…[48] Also by utilizinga monomer bearing as p 3 -core, Bçrjesson et al developed ac ontinuous flow method based on non-reversible coupling chemistry to prepare smooth continuous films 3D POPs. [49] In an attemptt oo vercomet he necessity of sp 3 carbons and coupling chemistry in all-organic 3D semiconductors, Coskune tal. recently demonstrated the preparation of epoxide-bearing 3D POPs via the Diels-Alderc ycloaddition polymerization, which was subsequently aromatized to form af irst example of af ully sp 2 -hybridized 3D graphitic porous polymer.…”
Section: Semiconducting Popsmentioning
confidence: 99%
“…[48] Also by utilizinga monomer bearing as p 3 -core, Bçrjesson et al developed ac ontinuous flow method based on non-reversible coupling chemistry to prepare smooth continuous films 3D POPs. [49] In an attemptt oo vercomet he necessity of sp 3 carbons and coupling chemistry in all-organic 3D semiconductors, Coskune tal. recently demonstrated the preparation of epoxide-bearing 3D POPs via the Diels-Alderc ycloaddition polymerization, which was subsequently aromatized to form af irst example of af ully sp 2 -hybridized 3D graphitic porous polymer.…”
Section: Semiconducting Popsmentioning
confidence: 99%
“…This includes the classes of 2D ordered polymers (2DPs), 10 2D covalent-organic frameworks (2D COFs) 11 and 2D metal–organic frameworks (2D MOFs), 12 while excluding classical polymers and similar materials ( i.e. 2D conjugated microporous polymers, 13 porous aromatic frameworks 14 ) that do not possess mentioned crystalline order and narrow pore-size distribution. Further we also exclude non-porous coordination polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from adjusting the (co)monomer concentrations poured over the substrate, reaction temperature and residence time in the reactor can be key factors to control film properties. Notwithstanding the amorphous nature of the final material, a similar method was applied to form PAF films over prefunctionalized substrates [57], and the findings showed that flow chemistry helped to improve film quality with respect to the previously published bulk method [58].…”
Section: Techniques For Covalent Organic Framework Film Formationmentioning
confidence: 99%